Homogeneous Assay of rs4343, an ACE I/D Proxy, and an Analysis in the British Women's Heart and Health Study (BWHHS). Issue 1 (2008) - Abdollahi, Mohammad Reza; Huang, Shuwen; Rodriguez, Santiago; Guthrie, Philip Alexander Isles; Smith, George Davey; Ebrahim, Shah; Lawlor, Debbie A.; Day, Ian N. M.; Gaunt, Tom R.
Abstract : Current literature suggests that ACE SNP rs4343, ACE 2350A>G in exon 17, T202T, may be the best proxy for the ACE Alu I/D whereas rs4363 and rs4362 may be slightly stronger predictors of ACE levels. Considering reported difficulties in genotyping ACE I/D and stronger associations of rs4343 than ACE I/D with plasma ACE levels in Africans, and suitability of rs4343 for allelic mRNA (cDNA) studies, we developed and validated a liquid phase assay for rs4343, which has advantage on both functional and technical grounds. We confirmed that rs4343, is in near perfect linkage disequilibrium (D'=1, r 2 =0.88, n=64) with ACE I/D in Europeans (A and G alleles of rs4343 marking insertion and deletion alleles of ACE I/D respectively). We then studied its association with metabolic and cardiovascular traits in 3253 British women (60–79 years old). Apart from a nominal trend of association with diastolic blood pressure (p anova=0.08; p trend=0.05), no other associations were observed. A post-hoc vascular and general phenome scan revealed no further associations. We conclude that ACE I/D is not a major determinant of metabolic and cardiovascular traits in this population. Liquid phase genotyping of SNP rs4343 may be preferable to gel based ACE I/D genotyping both for technical and functional reasons.